Effect of chronic kidney diseases-associated pruritus on patients’ sleep quality, well-being and its management - Inayat Ur Rehman; Tahir Mehmood Khan (Progress in Microbes and Molecular Biology)
Chronic kidney diseases-associated pruritus (CKD-aP) affects the patients’ mental and physical health, potentially resulting in fatigue, depression, and directly affecting quality of sleep. Hemodialysis patients were reported to experiencing moderate to extreme CKD-aP, thus exhibited higher possibilities of remaining awake at night while sleeping in the day. Therefore, CKD-aP is attributed toward nocturnal awakenings and difficulty falling asleep. This condition (CKD-aP) significantly impacts the quality of life (QOL), triggering sleep disturbance, mood changes, and uncontrollable scratching. CKD-aP patients have a compromised QOL that is generally linked to limited personal freedom and control due to lengthy treatment time. Overall, the loss of freedom has wider implications, such as altering marital, family, and social relationships. Thus, this writing highlights the vital effect of chronic kidney diseases-associated pruritus on patients’ sleep quality, social and mental well-being and providing comprehensive management and treatment options to improve patients’ quality of life.